Mortality from acute pancreatitis in Brazil from 2013 to 2023 (Research, Society and Development, 2024)
Acute Pancreatitis (AP) is defined as an inflammatory disease of the pancreatic gland, due to the action of partially activated enzymes, causing edema, hemorrhage and even pancreatic and peripancreatic necrosis, thus, the objective of this study is to quantitatively analyze the amount of deaths due to acute pancreatitis in Brazilian hospitals in the five regions of the country, in the period between January 2012 and September 2023. Methodology: a descriptive cross-sectional epidemiological study was carried out based on the SUS health information department (DATA/SUS) using as variables: hospital admissions, mortality rate, deaths, age group, color/race, sex, type of care and health macro-region, average hospital stay. Results: acute pancreatitis caused the deaths of 19,867 Brazilians during the period from 2012 to 2023. From data analysis, it was possible to observe a greater concentration of deaths in the southeast region of the country, of men between 60 and 69 years old. Conclusion: it is possible that several factors corroborate this finding, such as social and demographic characteristics, aspects linked to lifestyle and environmental exposure, as well as better access to diagnostic services, when compared to other Brazilian regions.